Cerium oxide/polydimethylsiloxane composite tapered fiber saturable absorber for mode-locked pulsed erbium-doped fiber laser - Mansor, Maisarah; Zainol Abidin, Nadiah Husseini; Liew, Josephine Ying Chyi; Alresheedi, Mohammed Thamer; Garg, Amit Kumar; Janyani, Vijay; Mahdi, Mohd Adzir (Elsevier, 2022)
This investigation demonstrates the nonlinear saturable absorption of cerium oxide (CeO2) nanoparticles; a lanthanide allotrope oxide material and its employment as a saturable absorber (SA) for the generation of stable mode-locked pulsed fiber laser. The CeO2 nanoparticles were simply prepared by sonicating its bulk solution and incorporating a polydimethylsiloxane (PDMS) polymer to form a thin film nanocomposite on tapered optical fiber for the fabrication of CeO2/PDMS-SA. The nonlinear intensity-dependent transmission characteristic of this material was confirmed with a modulation depth of 0.66% and saturation intensity of 77 MW/cm2. The SA was integrated into an erbium-doped fiber laser cavity, where mode-locking operation self-started at 35 mW pump power with stable soliton operation up to 250 mW in net anomalous dispersion regime. The pulse laser centered at 1561 nm wavelength with a constant repetition rate of 7.64 MHz, shortest pulse width of 800 fs, and highest signal to noise ratio of 54.2 dB. The highest pulse energy of 0.645 nJ and average power of 4.92 mW were measured at 250 mW pump power. Based on its simple preparation and stable pulse generation, this investigation suggests the viability of CeO2 nanoparticles as a new SA material for ultrashort pulse generation.